1999
DOI: 10.1292/jvms.61.961
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Serum Biochemical Values and Marbling Scores in Japanese Black Steers.

Abstract: ABSTRACT. In order to obtain available biochemical parameters related to the marbling score (MS), by which the meat was graded from 1 to 12 in Japan, serum biochemical values were examined in 13 Japanese Black steers during the fattening stages. The steers were divided into high MS (8-11) and low MS (4-5) groups and the fattening stage was also divided into 4 stages according to their feed contents; Stage I (11-13 month-old; 0-4 months after the fattening (af)), II (5-9 months af), III (10-14 months af), and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 13 publications
3
34
0
Order By: Relevance
“…However, results were not very promising, excepting for TC, in pigs (Tremere et al, 1966), and for TG and GLU, in cattle (Adachi et al, 1999;Hocquette et al, 1999), where these lipid indicators displayed a positive correlation with fat deposition traits. Steele et al (1972) found that the Duroc pigs selected against BT showed lower levels of serum GLU and TC than those selected for increased levels, and Etherton and Kris-Etherton (1980) encountered a marked alteration in the plasma lipoprotein composition between lean and obese swine.…”
Section: Discussionmentioning
confidence: 91%
“…However, results were not very promising, excepting for TC, in pigs (Tremere et al, 1966), and for TG and GLU, in cattle (Adachi et al, 1999;Hocquette et al, 1999), where these lipid indicators displayed a positive correlation with fat deposition traits. Steele et al (1972) found that the Duroc pigs selected against BT showed lower levels of serum GLU and TC than those selected for increased levels, and Etherton and Kris-Etherton (1980) encountered a marked alteration in the plasma lipoprotein composition between lean and obese swine.…”
Section: Discussionmentioning
confidence: 91%
“…This suggests that muscle and non-muscular adipose tissue interplay during the process of IMF accumulation, through hormonal changes such as thyroid hormones (Cassar-Malek et al, 2007b) and the insulin-glucose axis , which have been shown to be important in the differentiation of bovine muscles for instance. Attempts have been made to predict IMF level from blood parameters (Adachi et al, 1999). For instance, double-muscled bovines with low IMF level are characterized also by lower triiodothyronine, insulin and glucose plasma concentrations (Hocquette et al, 1999) than normal animals of the same breed.…”
Section: How Might Marbling Begin?mentioning
confidence: 99%
“…They proved that the correlation between the concentration of calcium, the amount of vitamin D 3 and the tenderness of meat evaluated by shearing tests was significant (p < 0.05). Adachi et al (1999) evaluated the correlation between the concentration of blood serum components and marbling of meat of steers and they proved the effect of glucose concentration on meat marbling.…”
Section: Discussionmentioning
confidence: 99%